Analisis Keautentikan dan Keunikan Laksa Cihideung Sebagai Kuliner Unggulan Kota Bogor - Heni Pridia Rukmini Sari (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2017)
The purpose of this research was studying authenticity and uniqueness of Laksa Cihideung as distinctive culinary. This research focuses on the food authenticity and unique that is defined as the originality and genuine of Laksa Cihideung in various aspects. It is an important element in portraying the identity, culture, and heritage of Laksa Cihideung.The research methodology employed in the present research was descriptive. The number of 35 questionnaires according to cluster and simple random sampling was filled out by participants. Hence, in-depth interviews were individually conducted among the food experts and questionnaire participants to seek how they interpret the meaning and characteristics of authenticity and uniqueness in Laksa Cihideung that influenced the taste of the food. The data gathered through the questionnaire were analyzed via SPSS 20.0. Based on the findings of this research, Laksa Cihideung has a great influence on attracting tourists to a destination from its authenticity and uniqueness.